The Improving of the Quality Resources of Gedog Batik Craftsmen in Tuban Regency - Muslichah Erma Widiana; Nova Retnowati; Agus Slamet; Tri Sagirani (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to improve business management of partner business UD. Batik